2022
DOI: 10.1136/bmjopen-2022-064979
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of post-COVID syndrome and associated symptoms in outpatient care in Bavaria, Germany: a retrospective cohort study using routinely collected claims data

Abstract: ObjectivesTo estimate the treatment incidence of post-COVID syndrome (postinfectious sequelae present at least 12 weeks following infection) in the context of ambulatory care in Bavaria, Germany, and to establish whether related diagnoses occur more frequently than in patients with no known history of COVID-19.DesignRetrospective cohort analysis of routinely collected claims data.SettingAmbulatory care in Bavaria, Germany, observed from January 2020 to March 2022 (data accessed May 2022).Participants391 990 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 29 publications
2
21
0
1
Order By: Relevance
“…Attempt to contact authors to obtain the data was not successful. Cohen 2022 [ 36 ] United States UnitedHealth Database Jan 2020 to Dec 2020 Retrospective cohort N = 226,380 Median (IQR) – 78 (30–175) days Mixed 65+ 58% 27 6.4 Concurrent No confirmed/ suspected SARS-CoV-2 infection Cardiovascular disease (acute coronary disease, cardiogenic shock, cardiac arrhythmia, cardiomyopathy, congestive heart failure, coronary disease, hypertension, myocardial infarction, tachycardia); Chronic kidney disease; Diabetes (type 2); Mental disorders (mental health diagnosis, psychosis); Neurological conditions (dementia, encephalopathy, Guillain-Barre syndrome, migraine, peripheral neuropathy, seizure); Respiratory disorders (chronic respiratory failure, interstitial lung disease); Stroke Daugherty 2021 [ 37 ] United States UnitedHealth Database Jan 2019 to Oct 2020 Retrospective cohort N = 488,552 Median (IQR) – 87 (45-124) days Mixed 18–65 52.5% 8.2 1.1 Concurrent No confirmed/ suspected SARS-CoV-2 infection Cardiovascular disease (acute coronary disease, arrythmia, cardiogenic shock, cardiomyopathy, congestive heart failure, coronary disease, hypertension, myocardial infarction, tachycardia); Chronic kidney disease; Diabetes (type 2); Mental disorders (mental health diagnosis, psychosis); Neurological conditions (Alzheimer’s disease, dementia, encephalopathy, Guillain-Barre syndrome, migraine, peripheral neuropathy, seizure); Respiratory disorders (chronic respiratory failure, interstitial lung disease); Stroke Donnachie 2022 [ 38 ] Germany Bavarian COVID-19 Cohort Jan 2020 to Jun 2021 Retrospective cohort N = 454,649 NR Followed up for 2 years Outpatient 0–60+ 54% NA Concurrent >90% had test negative Mental disorders (anxiety disorders, mood disorders); Neurological conditions (mild cognitive impairment) Jacob 2022 [ 39 ] Germany IQVIA Disease Analyzer database …”
Section: Resultsmentioning
confidence: 99%
“…Attempt to contact authors to obtain the data was not successful. Cohen 2022 [ 36 ] United States UnitedHealth Database Jan 2020 to Dec 2020 Retrospective cohort N = 226,380 Median (IQR) – 78 (30–175) days Mixed 65+ 58% 27 6.4 Concurrent No confirmed/ suspected SARS-CoV-2 infection Cardiovascular disease (acute coronary disease, cardiogenic shock, cardiac arrhythmia, cardiomyopathy, congestive heart failure, coronary disease, hypertension, myocardial infarction, tachycardia); Chronic kidney disease; Diabetes (type 2); Mental disorders (mental health diagnosis, psychosis); Neurological conditions (dementia, encephalopathy, Guillain-Barre syndrome, migraine, peripheral neuropathy, seizure); Respiratory disorders (chronic respiratory failure, interstitial lung disease); Stroke Daugherty 2021 [ 37 ] United States UnitedHealth Database Jan 2019 to Oct 2020 Retrospective cohort N = 488,552 Median (IQR) – 87 (45-124) days Mixed 18–65 52.5% 8.2 1.1 Concurrent No confirmed/ suspected SARS-CoV-2 infection Cardiovascular disease (acute coronary disease, arrythmia, cardiogenic shock, cardiomyopathy, congestive heart failure, coronary disease, hypertension, myocardial infarction, tachycardia); Chronic kidney disease; Diabetes (type 2); Mental disorders (mental health diagnosis, psychosis); Neurological conditions (Alzheimer’s disease, dementia, encephalopathy, Guillain-Barre syndrome, migraine, peripheral neuropathy, seizure); Respiratory disorders (chronic respiratory failure, interstitial lung disease); Stroke Donnachie 2022 [ 38 ] Germany Bavarian COVID-19 Cohort Jan 2020 to Jun 2021 Retrospective cohort N = 454,649 NR Followed up for 2 years Outpatient 0–60+ 54% NA Concurrent >90% had test negative Mental disorders (anxiety disorders, mood disorders); Neurological conditions (mild cognitive impairment) Jacob 2022 [ 39 ] Germany IQVIA Disease Analyzer database …”
Section: Resultsmentioning
confidence: 99%
“…For example, a Mediterranean cohort study found that approximately 50% of patients had persistent symptoms 10–14 weeks after the first episode 36 , while a Jordanian study showed that 71.8% of patients still have one physical or psychological symptom 3 months or more after the first infection 37 . In two German studies, 14.2% of patients developed post-COVID-19 symptoms 38 , whereas 27.8% of non-hospitalized COVID-19 patients reported at least one symptom 4 months after the initial symptom 3 . The differing results could be attributed to the various types of studies used, the length of follow-up, vaccination rates, and healthcare system differences.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of post-COVID syndrome varies across different patient populations, estimated at 10– 30% among non-hospitalized cases, 50–70% among hospitalized cases, and 10–12% among vaccinated cases, however clear diagnostic criteria are still lacking making precise estimates difficult [33, 34]. PCS affects individuals of all ages, with the highest percentage of diagnoses typically observed between the ages of 36 and 50 years, with a noteworthy observation that the relative frequency of PCS cases is highest among in non-hospitalized patients [9, 35].…”
Section: Discussionmentioning
confidence: 99%